Barriers to the Enforcement of Environmental Law: An Effect of Free Market Domination and Regional Autonomy in Indonesia - Mahoro, Jean Claude Geofrey; Samekto, F.X. Adji (Faculty of Law, Hasanuddin University, 2021)
This paper discusses different issues relating to the enforcement of environmental law in Indonesia in the long way of the Indonesian government to sustainable development. To reach reliable conclusion, socio-legal approach was employed in this paper. Throughout the work the researcher analyses environmental philosophies including anthropocentrism, biocentrism and ecocentrism. This phenomenon does not only pose responsibility to the government but also to private individuals or companies in their operations in order not to leave burdens to the shoulders of future generations. This ideology was not well ensured in the free-market economy and regional autonomy as the proliferated regulations were not directed to meet the efficient and equitable environmental principles. Hindrances to the effective implementation of environmental law, inter alia, the non-envisaged licensing system in administrative enforcement; ineffective civil damages towards the environmental losses; and non-reaching environmental criminal liability. Besides that, the persistent corruption is another impediment to the effective implementation of environmental law in Indonesia.Â